A simple model of service offshoring with time zone differences - Toru Kikuchi; Ngo Van Long (Center for Economic Studies and ifo Institute (CESifo), 2010)
We propose a two-country monopolistic competition model of business service offshoring that captures the advantage conferred by time zone differences. We emphasize the role of the entrepreneurs, who decide how to produce business services (i.e., domestic service provision or service offshoring). It is shown that the utilization of communication networks induces a dramatic change in industrial structure due to entrepreneurial relocation (i.e., service offshoring) to take advantage of time zone differences. We also show that in the presence of moving costs for entrepreneurs, technological improvements and the resulting increase in service offshoring may reduce a country's welfare.
Keywords: F12; 330; service offshoring; time zone differences; technological change; entrepreneurs; communication networks; Internationaler Dienstleistungsverkehr; Zwei-Länder-Modell; Zeit